An Investigation and Optimization of Hardness and Tribological Behaviour of Ricehusk Ash Reinforced Aluminium Matrix Composite using Powder Metallurgy Route (International Journal of Engineering Materials and Manufacture, 2025)
A composite material of pure aluminium (Al) reinforced with rice husk ash (RHA) was developed using the powder metallurgy route. The mixing parameters (speed and time) were optimized using optimum mixture design in Design Expert 13 software. The effects of varying aluminium and RHA compositions, as well as mixing time and stirring speed, were investigated. The mechanical and tribological properties, specifically hardness, wear rate and coefficient of friction (COF) were evaluated. Before the RHA reinforcement was added, the pure aluminium exhibited a hardness of 61.36666667 HV, a wear rate of 0.000013889 mm/Nm, and a coefficient of friction of 0.3215. The optimization process resulted in an optimal composition of 12.552% RHA and 87.448% aluminium, with a stirring speed of 169.812rpm and a mixing time of 1 hour. Under these conditions, the composite achieved a hardness of 108.326 HV, a zero wear rate, and a coefficient of friction of 0.307. The optimization led to a percentage improvement of 76% in hardness, a 100% reduction in wear rate, and a 4.1% reduction in coefficient of friction. The reduced coefficient of friction remains within the optimal range for effective braking application.